The Legal and Jurisprudential Effects of a Provisional Agreement on Immovable Properties - Hejazifar, Ebrahim; Salimi, Dr. Mahnaz; Hasankhani, Dr. Razieh (The journal of contemporary issues in business and government, 2021)
Real estate transactions without a formal document are important issues that happen a lot. In the case of property, according to Article 22 of the Registration Law: "....... the government will recognize only the person in whose name the property is registered or the person to whom the property has been transferred and is the owner." Today, most real estate transactions are normal, and conflicts between social realities or registration rules, etc., have caused many problems in society, especially in the courts of law. Transfers relating to the interests of the property must be registered. Otherwise, in accordance with Article 48 of the said law, such documents will not be accepted in any of the departments and courts. The role of the deed in real estate transactions is such that it can be said that most of such transactions are established and realized by the deed. What is certain is that the deed has always been and is common in transactions and as a document. Ordinary and a contract of commitment to make a sale valid in the future Article 10 of the Civil Code stipulates that private contracts are valid for those who have concluded it, unless it is explicitly against the law. Many lawyers believe that the above article the reasons for the necessity of fulfilling the contracts, in addition to certain contracts, also include indefinite contracts, and one of the most important of these contracts is the contract of commitment to form a sale in the future, which is generally regulated in the form of an ordinary document. On the other hand, one of the topics emphasized by the Holy Quran and the Holy Prophet of Islam and the Imams of the Infallible has been the issue of fulfilling the covenant and the necessity of fulfilling the obligations of individuals towards each other. It has been proven that according to the reasons presented, the verdict of accuracy is apparently more correct and there are jurisprudential reasons for this.